Synthesis of various dimensional metal organic frameworks (MOFs) and their hybrid composites for emerging applications – A review. (July 2022) - Annamalai, Jayshree; Murugan, Preethika; Ganapathy, Dhanraj; Nallaswamy, Deepak; Atchudan, Raji; Arya, Sandeep; Khosla, Ajit; Barathi, Seetharaman; Sundramoorthy, Ashok K.
Abstract: Metal organic frameworks (MOFs) represent the organic and inorganic hybrid porous materials. MOFs are low dense and highly porous materials which in turn provide large surface area that can accumulate and store numerous molecules within the pores. The pore size may also act as a mesh to separate molecules. The porous nature of MOFs is beneficial for altering the intrinsic properties of the materials. Over the past decade, different types of hybrid MOFs have been reported in combination with polymers, carbon materials, metal nanoparticles, metal oxides, and biomolecules for various applications. MOFs have also been used in the fabrication of electronic devices, sensors, energy storage, gas separation, supercapacitors, drug delivery and environmental clean-up. In this review, the unique structural orientation, exceptional properties and recent applications of MOFs have been discussed in the first section along with their porosity, stability and other influencing factors. In addition, various methods and techniques involved in the synthesis and designing of MOFs such as solvothermal, electrochemical, mechanochemical, ultrasonication and microwave methods are highlighted. In order to understand the scientific feasibility of MOFs in developing new products, various strategies have been applied to obtain different dimensional MOFs (0D, 1D, 2D and 3D) and their composite materials are also been conferred. Finally, the future prospects of MOFs, remaining challenges, research gaps and possible solutions that need to be addressed by advanced experimental design, computational models, simulation techniques and theoretical concepts have been deliberated. Graphical abstract: Image 1 Highlights: Metal organic frameworks (MOFs) comprises metallic centers and multitopic organic units forming infinite arrays. MOFs have more than thousands of structural orientations appealing to various applications. Novel synthesis of 0D, 1D, 2D and 3D MOFs involve various nano-composite materials and decoration of nanoparticles. Application includes fabrication of sensors, energy storage, gas separation, drug delivery, environmental clean-up and others. Further developments in MOF would resolve more environmental issues; however, green synthesis and safe disposal to be considered.